2016
DOI: 10.1111/jgh.13273
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillectomy and the risk of inflammatory bowel disease: A systematic review and meta‐analysis

Abstract: This meta-analysis demonstrates that tonsillectomy is associated with an increased risk of developing CD. We found no evidence to suggest that tonsillectomy exerts a protective effect on the development of UC, as is the case with appendectomy. Further prospective studies are required to confirm the validity of these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 58 publications
1
36
1
Order By: Relevance
“…Campylobacter in saliva was negatively correlated with Haemophilus in tonsils. Previously, a meta-analysis suggested that tonsillectomy is associated with an increased risk of developing Crohn's disease 42 , which is a major form of inflammatory bowel disease with a high prevalence of Campylobacter, particularly in pediatric patients 43 . It remains unclear why tonsillectomy is associated with an increased risk for developing this specific inflammatory bowel disease, but it seems that the negative correlation between Campylobacter and Haemophilus in our data could be considered as one possible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter in saliva was negatively correlated with Haemophilus in tonsils. Previously, a meta-analysis suggested that tonsillectomy is associated with an increased risk of developing Crohn's disease 42 , which is a major form of inflammatory bowel disease with a high prevalence of Campylobacter, particularly in pediatric patients 43 . It remains unclear why tonsillectomy is associated with an increased risk for developing this specific inflammatory bowel disease, but it seems that the negative correlation between Campylobacter and Haemophilus in our data could be considered as one possible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Tonsillectomy was associated with subsequent CD (OR, 1.37; 95% CI, 1.16-1.62) but not UC or IBD ( Figure 2 and Supplementary Tables 1-3). 35,36 However, antibiotic exposure may be an unmeasured confounder (individuals having tonsillectomy have often experienced previous exposure to antibiotics).…”
Section: Surgeriesmentioning
confidence: 99%
“…In this edition of the Journal of Gastroenterology and Hepatology, Sun et al have performed a meta-analysis of 23 observational studies (22 UC and 17 CD) in an attempt to draw more definitive conclusions as to the effect of tonsillectomy on the subsequent development of IBD. 10 The results of this meta-analysis found a significant positive association between tonsillectomy and the subsequent development of CD (OR 1.37, 95% CI: 1.16-1.62) but no relationship between tonsillectomy and UC (OR 0.94, 95% CI: 0.84-1.05). This is in direct contrast to the consistent protective effect of appendicectomy in UC seen in many case-control studies.…”
mentioning
confidence: 72%
“…In this edition of the Journal of Gastroenterology and Hepatology , Sun et al . have performed a meta‐analysis of 23 observational studies (22 UC and 17 CD) in an attempt to draw more definitive conclusions as to the effect of tonsillectomy on the subsequent development of IBD …”
Section: Inflammatory Bowel Disease Risk and The Environment: Where Tmentioning
confidence: 99%